KODE SASTRA, KODE BAHASA, DAN KODE BUDAYA DALAM CERITA PENDEK “SENYUM KARYAMIN” KARYA AHMAD TOHARI - Fatimatu Seha, Ghina Nasuha (University of Brawijaya, 2023)
This article presents the results of research on allusions in a short story entitled “Senyum Karyamin” by Ahmad Tohari. This research analyzes language code, literary code, and cultural code. The approach taken is a textual approach which emphasizes its analysis on the linguistic side of understanding texts. The data source is from Ahmad Tohari’s short story, “Senyum Karyamin”. The results of the analysis of the short story